Successful Primary Medical Therapy with Somatostatin Receptor Ligand in Acromegaly with Thyroid Cancer - Shalini Sree Dharan; Nor Azmi Kamaruddin (Journal of the ASEAN Federation of Endocrine Societies, 2017)
Acromegaly is a rare disease with an annual incidence of 3 to 4 cases in a million.[1] Diagnosis is often delayed due to the slow progression of the disease. Persistent elevation of growth hormone (GH) in acromegaly causes a reduction in life expectancy by 10 years. Aside from multiple cardiovascular, respiratory and metabolic co-morbidities, it has also been proven to cause an increased incidence of cancer. The main treatment of acromegaly is surgical excision of the functioning pituitary adenoma. Multiple comorbidities, including obstructive sleep apnea (OSA), left ventricular hypertrophy (LVH) and soft tissue swelling, make surgery complicated, if not impossible. Medical therapy to reduce co-morbidities may be indicated in certain situations. Somatostatin receptor ligands (SRL) are able to reduce, and possibly normalize, IGF-1 levels.[2] Reduction of insulin-like growth factor-1 (IGF-1), the main mediator of GH, is able to resolve headache, sweating, fatigue and soft tissue swelling, and also reduce ventricular hypertrophy. This case report illustrates the successful use of the SRL octreotide LAR in treating acromegaly. It also confirms the observation from several case series that thyroid cancer is the most common malignancy in acromegaly.